A methodology of investment appraisal for third-level airlines - Garner, J. D. (Cranfield University, 1980)
Third-level airlines are approached as a financial system composed of models of travel demand and cost. The models are formulated by multiple regression, subjective probability distributions, and weighted random-walk techniques because these techniques result in probability distributions which may be input into a risk analysis program. The risk analysis program is used to investigate the cash required to start, by the method of "Optimum Coverage", an example third-level airline in Oregon. The risk analysis program is also used to analyze the airline as an investment and to determine the proper method of finance. The airline required from $4.2 million to $6.1 million dollars to begin operations and had expected internal rates of return from 25% to 62% depending on the method of finance. The analysis shows that the airline performs best as a tax shelter and that in every instance, with an average weighted cost of capital exceeding 2.0%, the airline should exchange tax benefits (either as a tax shelter or by leasing aircraft) for more favorable financial terms. New travel demand forecasting methods investigated included a method for combining the flight frequency, the time of desired departures, and the difference between mode travel times into a single independent variable; and a method for combining population, income, and the distribution of personal income into a single independent variable. Hence, a single independent variable may account quantitatively for the effects of several variables when only a small data base is available. The short-haul nature of the third-level airline routes were found to make traffic more sensitive to quality-of-service variables than price, and the costs of third-level airlines were best determined by the revenue-passenger-miles they produced. The reserve aircraft problem and the service levels of engines and avionics are determined using the concept of affordable risk. Rate Per Hour Contracts are beneficial for the small operator for avionics, but they are beneficial for engines only if there is also an exchange agreement.